Assessment of quality indicators for acute myocardial infarction management in 28 countries and use of composite quality indicators for benchmarking. Issue 8 (December 2020) - Rossello, Xavier; Medina, Jesús; Pocock, Stuart; Van de Werf, Frans; Chin, Chee Tang; Danchin, Nicolas; Lee, Stephen W-L; Huo, Yong; Bueno, Héctor
Background: The European Society of Cardiology established a set of quality indicators for the management of acute myocardial infarction. Our aim was to evaluate their degree of attainment, prognostic value and potential use for centre benchmarking in a large international cohort. Methods: Quality indicators were extracted from the long-tErm follow-uP of antithrombotic management patterns In acute CORonary syndrome patients (EPICOR) (555 hospitals, 20 countries in Europe and Latin America, 2010–2011) and EPICOR Asia (218 hospitals, eight countries, 2011–2012) registries, including non-ST-segment elevation acute myocardial infarction ( n =6558) and ST-segment elevation acute myocardial infarction ( n =11, 559) hospital survivors. The association between implementation rates for each quality indicator and two-year adjusted mortality was evaluated using adjusted Cox models. Composite quality indicators were categorized for benchmarking assessment at different levels. Results: The degree of attainment of the 17 evaluated quality indicators ranged from 13% to 100%. Attainment of most individual quality indicators was associated with two-year survival. A higher compliance with composite quality indicators was associated with lower mortality at centre-, country- and region-level. Moreover, the higher the risk for two-year mortality, the lower the compliance with composite quality indicators. Conclusions: When EPICOR and EPICOR Asia were conducted, the European Society of Cardiology quality indicators would have been attained to a limited extent, suggesting wide room for improvement in the management of acute myocardial infarction patients. After adjustment for confounding, most quality indicators were associated with reduced two-year mortality and their prognostic value should receive further attention. The two composite quality indicators can be used as a tool for benchmarking either at centre-, country- or world region-level.